Kamalapatrẽ : Nā. Sī. Phaḍake yānī pravāsāntūna Kamalābāīnā pāṭhavilel̃ī patrẽ - Phadke, Narayan Sitaram (SAMP early 20th-century Indian books project, 1949)
Letters written during his travel to various places to his wife Kamala Phadke.